LGBT Sexual Disorientation in East Java Region(Sexual education deviant in a city in East Java) - Siti Mahmudah Noorhayati; Abd. Hafid (Attanwir : Jurnal Keislaman dan Pendidikan, 2024)
The aim of this research is to understand the background and sexual behavior of LGBT teenagers in a city located in the East Java region that has sexual disorientation. Sexual disorientation is the physical attraction, emotional arousal, romantic and sexual interest of a person towards others that disregards their sexual identity (biological sex) and sexual behavior. Homosexuality is a condition in which a person exhibits sexual behavior between individuals of the same sex. The teenage years are a transitional period marked by physical and psychological changes from childhood to adulthood. In each developmental period, there are a number of developmental tasks that must be completed.  This type of research is qualitative research with a phenomenological approach using snowball sampling technique. Data collection in this research utilized interview, observation, and documentation techniques conducted with 5 gay teenagers. Data analysis began with observation and documentation, followed by in-depth interviews with key informants. That is someone who truly understands and knows the situation of the research object. After conducting the interview, data analysis begins by creating a transcript of the interview results, by playing back the recording of the interview, listening carefully, and then writing down the words heard according to what is on the recording. The results of this study indicate that the background of LGBT adolescents in a city located in East Java is influenced by personality traits that have developed since childhood, significant others, and reference groups. Meanwhile, the depiction of their behavior is relatively similar to that of teenagers who are dating the opposite sex, such as holding hands, hugging, and so on.